Ellipsometric investigation of β-Si₃N₄ ceramics with Mo and Al additives - Prokopets', V.M.; Shaykevich, I.A.; Robur, L.Y. (Functional Materials, 2005)
Ceramic Si₃N₄ samples with Мо and AI admixtures have been investigated by spectroellipsometry. The influence of admixtures on the ceramics optical properties have been studied. The local defects of Si₃N₄ crystal structure are responsible for the band gap reduction. The silicone oxynitride amount in the studied samples has been estimated numerically by Bruggeman effective medium approximation.